A review of the hybrid artificial intelligence and optimization modelling of hydrological streamflow forecasting - Ibrahim K.S.M.H. (Elsevier B.V., 2023)
Climate change; Fuzzy inference; Fuzzy neural networks; Fuzzy systems; Genetic algorithms; Hydrology; Particle swarm optimization (PSO); Reservoirs (water); Stream flow; Support vector machines; Water supply systems; Adaptive neuro-fuzzy inference system; Artificial bee colony; Artificial neural network; Genetic algorithm; Intelligence modeling; Optimization algorithms; Particle swarm optimization; Reservoir inflow; Streamflow forecasting; Support vector machine; Forecasting